C/C++ software quality tools - Murphy, Mark L. (Prentice Hall PTR, 1996)
Software testing is a critical stage in a product's climb to success or fall to failure. This book offers a practical approach to software quality assurance, with a special emphasis on the tools needed to assist in the process. The book covers the entire process from initial development to the final testing of a software product. It focuses on Continuous Improvement (CI) - the key for firms seeking ISO-9000 quality certification. It also teaches readers about the software testing process and how tools can help accelerate and enhance efforts to achieve better quality, shows how to build custom testing tools, and includes 6 testing tools and a sample application.